Tissue-specific pyruvate dehydrogenase complex deficiency causes cardiac hypertrophy and sudden death of weaned male mice - Sidhu, Sukhdeep (American Physiological Society, 2008)
Pyruvate dehydrogenase complex (PDC) plays an important role in energy homeostasis in the heart by catalyzing the oxidative decarboxylation of pyruvate derived primarily from glucose and lactate. Because various pathophysiological states can markedly alter cardiac glucose metabolism and PDC has been shown to be altered in response to chronic ischemia, cardiac physiology of a mouse model with knockout of the α-subunit of the pyruvate dehydrogenase component of PDC in heart/skeletal muscle (H/SM-PDCKO) was investigated. H/SM-PDCKO mice did not show embryonic lethality and grew normally during the preweaning period. Heart and skeletal muscle of homozygous male mice had very low PDC activity (∼5% of wild-type), and PDC activity in these tissues from heterozygous females was ∼50%. Male mice did not survive for >7 days after weaning on a rodent chow diet. However, they survived on a high-fat diet and developed left ventricular hypertrophy and reduced left ventricular systolic function compared with wild-type male mice. The changes in the heterozygote female mice were of lesser severity. The deficiency of PDC in H/SM-PDCKO male mice greatly compromises the ability of the heart to oxidize glucose for the generation of energy (and hence cardiac function) and results in cardiac pathological changes. This mouse model demonstrates the importance of glucose oxidation in cardiac energetics and function under basal conditions.